ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT WISATAWAN DI PANTAI MUTIARA INDAH DESA TANJUNG LIMAU KECAMATAN MUARA BADAK KABUPATEN KUTAI KARTANEGARA - Febri Agung Prasetio; Bambang Indratno Gunawan; Fitriyana (Jurnal Pembangunan Perikanan dan Agribisnis, 2021)
Mutiara Indah Beach has tourist attractions such as the beautiful white sand that stretches along the coast, with marine biota decoration scattered along the beach due to waves swept away. Fish types of grouper, trakulu, gulama, and snapper are often found in Pangempang waters. This research is intended to find out how much influence the tourist attraction and facilities have on the interest of tourists visiting the Mutiara Indah beach. The design of this study used a survey method with a questionnaire as a data collection tool and involved 30 tourist respondents who visited Mutiara Indah beach in October 2019. The data collected were analyzed using multiple linear regression analysis tools consisting of t test, F test, regression coefficient and classic assumption test (data normality test, data reliability test). The results of this study indicate that all independent variables (tourist attractiveness and facilities) have a positive and significant effect on the interest of tourists visiting the Mutiara Indah beach with each significance Travel Attraction = 0,000 and Facilities table = 0.006, and the significance of F starting = 0,000, at Pantai Mutiara Indah in 2019. It is recommended for Mutiara Indah Beach Managers to increase promotion or add other facilities so that Mutiara Indah beach is better known.